TRPM2: a candidate therapeutic target for treating neurological diseases - BELROSE Jillian Corinne; JACKSON Michael Frederick (Acta Pharmacologica Sinica, 2018)
Abstract Transient receptor potential melastatin 2 (TRPM2) is a calcium (Ca2+)-permeable non-selective cation channel belonging to the TRP ion channel family. Oxidative stress-induced TRPM2 activation provokes aberrant intracellular Ca2+ accumulation and cell death in a variety of cell types, including neurons. Aberrant TRPM2 function has been implicated in several neurological disorders including ischemia/ stroke, Alzheimer’s disease, neuropathic pain, Parkinson’s disease and bipolar disorder. In addition to research identifying a role for TRPM2 in disease, progress has been made in the identification of physiological functions of TRPM2 in the brain, including recent evidence that TRPM2 is necessary for the induction of N-methyl-D-aspartate (NMDA) receptor-dependent long-term depression, an important form of synaptic plasticity at glutamate synapses. Here, we summarize recent evidence on the role of TRPM2 in the central nervous system (CNS) in health and disease and discuss the potential therapeutic implications of targeting TRPM2. Collectively, these studies suggest that TRPM2 represents a prospective novel therapeutic target for neurological disorders.